Rootedness, belonging and life project: University organizational culture - Villamizar Carrillo, Diana Janeth; Mogollón Canal, Olga Mariela; Padilla Sarmiento, Sandra Licette; Villamizar Carrillo, Anyela Patricia (2025)
This book analyzes the categories of belonging, sense of belonging, and life plan in the context of public higher education, exploring their meaning for faculty and their impact on the organizational culture oriented toward academic excellence and lifelong human development. The research was based on a qualitative, exploratory, descriptive, and cross sectional methodology, which allowed for the description of the possibilities and opportunities, as well as the barriers and limitations, of the work, social, and individual environments. The techniques employed were interviews and open-ended questionnaires with incomplete sentences, using a population triangulation composed of managers, faculty, and experts.The conclusions highlight that organizational culture is shaped by the interaction of work dimensions, place of residence, the faculty member’s professional profile, and their personal well-being; this also extends to the family environment and romantic relationships. In this context, belonging and a sense of belonging emerge as key elements for both the academic context and the city, facilitating the development of a life plan in the short, medium, and long term. Thus, this research provides a comprehensive look at how these factors contribute to strengthening identity and commitment in higher education.
Keywords: Organizational climate; Human development; University adaptation; Roots; Sense of belonging; Public higher education